2013
DOI: 10.3389/fncel.2013.00263
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of CA3 spike phase response arising from h-current properties

Abstract: The phase of firing of hippocampal neurons during theta oscillations encodes spatial information. Moreover, the spike phase response to synaptic inputs in individual cells depends on the expression of the hyperpolarization-activated mixed cation current (Ih), which differs between CA3 and CA1 pyramidal neurons. Here, we compared the phase response of these two cell types, as well as their intrinsic membrane properties. We found that both CA3 and CA1 pyramidal neurons show a voltage sag in response to negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
(68 reference statements)
2
14
0
Order By: Relevance
“…As the duration of the inhibitory postsynaptic current (IPSC) is thought to determine the pace of the rhythm (Fisahn et al, 1998;Atallah & Scanziani, 2009), it is possible that the generators involve different interneurons which produce IPSCs of different durations thus resulting in gamma oscillations of different frequencies. An alternative explanation is that pyramidal neurons in CA3 have a longer time constant than those in CA1 (Borel et al, 2013). Moreover, pyramidal neurons in CA3 are highly recurrently connected (Lorente de N o, 1934) whereas the principal neurons in CA1 and in layer II of the mEC are not (Pastoll et al, 2013).…”
Section: Gamma Oscillation Frequencies In the Entorhinal-hippocampal mentioning
confidence: 99%
“…As the duration of the inhibitory postsynaptic current (IPSC) is thought to determine the pace of the rhythm (Fisahn et al, 1998;Atallah & Scanziani, 2009), it is possible that the generators involve different interneurons which produce IPSCs of different durations thus resulting in gamma oscillations of different frequencies. An alternative explanation is that pyramidal neurons in CA3 have a longer time constant than those in CA1 (Borel et al, 2013). Moreover, pyramidal neurons in CA3 are highly recurrently connected (Lorente de N o, 1934) whereas the principal neurons in CA1 and in layer II of the mEC are not (Pastoll et al, 2013).…”
Section: Gamma Oscillation Frequencies In the Entorhinal-hippocampal mentioning
confidence: 99%
“…The EC has been shown to be vital for spatial navigation (78) and SC inputs from CA3 to CA1 have been shown to be important for memory consolidation (79). Some regions of the hippocampus have been shown to be intrinsically oscillogenic, such as the CA3 region (44,59,(80)(81)(82). Furthermore, a recent study has shown that CA1 is also capable of generating intrinsic gamma oscillation in response to a theta input in addition to inheriting activity from the projections received from CA3 and EC (83).…”
Section: In Vitro Hippocampal Gamma Oscillationsmentioning
confidence: 99%
“…A different proposed phase code suggests that the biphasic ability of excitatory synaptic inputs to jitter the spike timing of CA1 and CA3 hippocampal pyramidal neurons phase-locked by a sinusoidal theta oscillation is useful for encoding memories [58]. The biphasic response is due to the unconventional protocol; when CA1 neurons are biased in a pacemaker regime they exhibit a monophasic PRC [11].…”
Section: Hippocampal Phase Codesmentioning
confidence: 99%